Effect of an educational program on nurses’ knowledge and practices toward Hepatitis B virus in emergency hospitals in Erbil City - Abdulla, Salih A.; Abdulla, Zhian A. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Nurses have major role in prevention and management of hepatitis B. Aim of the study was to find out the effect of an educational program on nurse’ knowledge and practices concerning hepatitis B virus. Methods: A quasi-experimental study was conducted in emergency hospitals, Erbil city, Iraq from 15th of January to 15th of June 2012 involving 50 nurses. Assessment of the knowledge and practices of nurses was carried out by using a questionnaire developed by the researchers. An educational program was designed, constructed and oriented in order to improve the nurses’ knowledge and practices towards hepatitis B virus. Post-test was carried out after the educational program using the same (pre program) questionnaire. Results: The mean (±SD) score of pre test knowledge was 6.96±1.6, while the mean (±SD) score of post test knowledge was 8.4±1.5 (P<0.001). The educational program has significant effects on nurses’ knowledge about main function of liver (P<0.001), complications of renal failure (P=0.002), and avoiding sharing needles and syringes (P=0.013). The post test means (±SD) scores for practices (47±2.46) were significantly higher than the pre-test mean score (43.7±5.16). The educational program had effects on advising practice of hand washing before and after using gloves (P=0.01), using solution for hand washing (P=0.003), risk of contamination with patients’ bloods and fluids (P=0.04), removing of gown and washing hands (P=0.012). Conclusion: The educational program played a significant role in some items which could raise the level of knowledge and practices toward prevention of hepatitis B virus.